PENCIPTAAN KARYA SENI DENGAN TEMA BODY SHAMING MENGGUNAKAN TEKNIK TEKSTIL IMBUHAN - Shafina Nurul Hidhayah; Tiwi Bina Affanti (Narada : Jurnal Desain dan Seni, 2021)
Physical bullying often occurs both on social media and on a daily basis. This action in the long term can have a negative impact on the victim, such as the emergence of excessive anxiety, shame, lack of confidence, to the emergence of eating disorders and other mental disorders. The phenomenon of physical bullying is manifested through a work of expression using textile affixing techniques. The stages of the design of the work carried out by the method of creation of works by SP Gustami through the exploration stage, the design stage and the embodiment stage. This artwork using additional textile techniques such as: quilting, slash quilt, decorative stitch, sewing, and application. The materials used include cotton, tile, flannel, embroidery thread, sewing thread, and others. Novelty textile chosen because it has a variety of techniques that are suitable for conveying messages in the work. This artwork express the sadness and gloomy feeling of the victims through Novelty textile.